2004
DOI: 10.1128/iai.72.12.6914-6923.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the N-Terminal Cytotoxicity Region of Clostridium perfringens Enterotoxin by Site-Directed Mutagenesis

Abstract: Clostridium perfringens enterotoxin (CPE) has a unique mechanism of action that results in the formation of large, sodium dodecyl sulfate-resistant complexes involving tight junction proteins; those complexes then induce plasma membrane permeability alterations in host intestinal epithelial cells, leading to cell death and epithelial desquamation. Previous deletion and point mutational studies mapped CPE receptor binding activity to the toxin's extreme C terminus. Those earlier analyses also determined that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 42 publications
4
87
0
Order By: Relevance
“…Application of recombinant CPE protein leads to the dose-dependent rapid eradication of claudin-4-or claudin-3-overexpressing pancreas, breast or colon cancer cells in vitro and in vivo. 17,18,[33][34][35][36][37] The intratumoral in vivo application of recombinant CPE did not induce toxinassociated side effects, supporting its great therapeutic potential. However, these approaches require repeated, almost continuous regional or loco-regional application of recombinant CPE at doses ranging from 0.5 to 1.0 mg CPE per application to achieve therapeutic effects.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Application of recombinant CPE protein leads to the dose-dependent rapid eradication of claudin-4-or claudin-3-overexpressing pancreas, breast or colon cancer cells in vitro and in vivo. 17,18,[33][34][35][36][37] The intratumoral in vivo application of recombinant CPE did not induce toxinassociated side effects, supporting its great therapeutic potential. However, these approaches require repeated, almost continuous regional or loco-regional application of recombinant CPE at doses ranging from 0.5 to 1.0 mg CPE per application to achieve therapeutic effects.…”
Section: Introductionmentioning
confidence: 76%
“…22,24,25 This binding leads to disintegration of plasma membrane in association with rapid cytolysis of treated cells. 34 Several in vitro and in vivo studies demonstrated the antitumoral activity of recombinant CPE, limited by the need for frequent, repeated CPE application to achieve antitumoral effects. 17,18 As a novel alternative Clostridium perfringens enterotoxin gene therapy W Walther et al approach, we were aiming at CPE gene therapy for improved and prolonged toxin action at lower dose as required for external CPE application.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those structural analyses, coupled with mutagenesis studies (56)(57)(58)(59)(60)(61), indicated that CPE contains a C-terminal domain that binds to claudin receptors on host cells and an N-terminal domain, consisting of two halves, that is critical for pore formation by mediating oligomerization and membrane insertion.…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%
“…Previous studies using CPE variants blocked for one or more CPE functions have provided important insights into the action of this toxin (8,10,16,17,32). Binding activity has been mapped to the extreme C terminus, based upon the binding ability of recombinant CPE (rCPE) fragments containing Cterminal sequences (8)(9)(10)(11) and the binding deficiencies of rCPE fragments lacking 5, 10, or 30 amino acids from the C terminus (17).…”
mentioning
confidence: 99%
“…The same study also identified a region between amino acids 45 and 53 of rCPE that is essential for cytotoxicity, since rCPE fragments lacking these 9 amino acids were unable to form a large complex or induce pore formation. A subsequent site-directed mutagenesis study fine mapped this N-terminal CPE cytotoxicity region and demonstrated that the aspartic acid at position 48 is essential for large-complex formation and cytotoxicity (32).…”
mentioning
confidence: 99%